2003
DOI: 10.1046/j.1365-2141.2003.04312.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoplatelet counting: potential for reducing the use of platelet transfusions through more accurate platelet counting

Abstract: Summary. Research is required to determine the optimal approach for prophylactic platelet transfusions in patients with haematological malignant disorders. It has been suggested that thresholds for prophylactic platelet transfusions of platelet counts below 10 × 109/l should be investigated, as these may be equivalent in clinical effectiveness and associated with lower costs and fewer complications. An important concern in such investigation is the accurate estimation of platelet counts below 10 × 109/l. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
21
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 14 publications
6
21
0
1
Order By: Relevance
“…Accuracy of a method can be determined by comparing the results of a particular analyzer with those obtained with a gold standard counting method. By definition, this status is currently assigned to a method based on staining PLTs with fluorescent conjugated CD61 antibodies and subsequent detection usually with a flow cytometer 10,12,13 . Because the sample is continuously diluted with sheath fluid, the exact sample volume that is counted is not known, and therefore RBCs are counted simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Accuracy of a method can be determined by comparing the results of a particular analyzer with those obtained with a gold standard counting method. By definition, this status is currently assigned to a method based on staining PLTs with fluorescent conjugated CD61 antibodies and subsequent detection usually with a flow cytometer 10,12,13 . Because the sample is continuously diluted with sheath fluid, the exact sample volume that is counted is not known, and therefore RBCs are counted simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that an accurate count (the reference method) in conjunction with a platelet transfusion threshold of 5 Â 10 9 /L could potentially decrease the number of platelet transfusions by 10.4%. However, conflicting results were obtained at higher thresholds and the investigators concluded that larger well-designed multicentre studies were required (11). The same group recently reported a multicentre evaluation of all currently available technologies in the United Kingdom (see below) (12).…”
Section: Independent Validation Of the Platelet/rbcmentioning
confidence: 99%
“…The investigators suggested that the patient population, sample selection, and reference method may have contributed to the discordance between this study and other evaluations (10). Another independent laboratory also utilised the RBC/platelet ratio and were confident to use this as a reference method for the comparison of Bayer and ABX counters (11). They concluded that an accurate count (the reference method) in conjunction with a platelet transfusion threshold of 5 Â 10 9 /L could potentially decrease the number of platelet transfusions by 10.4%.…”
Section: Independent Validation Of the Platelet/rbcmentioning
confidence: 99%
“…1 This reduction would conserve valuable stocks of platelets for transfusion and reduce the exposure of patients to the risks associated with transfusion of blood components. The accuracy of platelet counts produced by routine automated hematology analyzers has been questioned, [2][3][4] and the limitations of platelet counting at these extremely low levels should be understood by people responsible for the care of patients.…”
mentioning
confidence: 99%